Effect of offline bullying on online unethical behavior among college students: the mediating roles of relative deprivation and anger rumination - Lin, Ying; Tang, Zhiwen; Xing, Qiang (Frontiers in Psychology, 2024)
This research delves into the correlation between offline bullying and online unethical behavior among college students; and examines the potential mediating influences of anger rumination and perceived relative deprivation. The findings suggest that anger rumination, perceived relative deprivation, offline bullying, and online unethical behavior exhibit significant positive correlations with each other. (2) Offline bullying significantly predicts online unethical behavior among college students, with the dual mediating effects of perceived relative deprivation and anger rumination on the relationship between offline bullying and online unethical behavior. This suggests that offline bullying directly influences college students' online unethical behavior and also influences it indirectly through anger rumination and perceived relative deprivation.paper is the result of the stage research "Research on the Influence Mechanism of College Students' Online Moral Demonstration Behavior and Moral Boosting" (No. GD20XJY25), a discipline co-construction project of philosophy and social science of Guangdong Province "13th Five-Year Plan" in 2020; and Guangdong Social Science Planning 2021 Project Construction of the Value-added Evaluation system for Adolescents' Mental Health based on Digitalization (No.